Modularisation in the German VET system: a study of policy implementation - Li, Junmin [Verfasser]; Pilz, Matthias [Verfasser] (My University, 2017)
"Modularisation of vocational training courses is a major issue across many European countries. Germany has been slow to implement modularisation in its VET system: the prevailing view of modular concepts in the country is one of great scepticism, but there is very little empirical data to inform the debate. This exploratory study focuses on the relationship between the regulatory goals that underpin the introduction of modular VET systems and the implementation in practice of two VET programmes (elective skills and training building blocks). Our analysis includes official descriptions of training programmes, research papers, evaluation reports and policy papers. We also conducted a total of 12 interviews with experts at policy level and 25 interviews with practitioners. The findings indicate that Germany's approach to implementing modularisation is a hybrid, rather than a radical, approach in which differing degrees of emphasis are evident. The hypothesised goals of flexibilisation and specialisation are broadly achieved, but the goal of individualisation is only partially achieved. In this respect, certification and recognition of modules seem to be the greatest challenges." (authors' abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 2.3 Berufsbildungspolitik; Berufsbildungspolitik; Berufsausbildung; Modularisierung; Flexibilisierung